Energy Research Infrastructures in Europe and Beyond: Mapping an Unmapped Landscape - Knudsen Mikkel Stein; Birmoser Ferreira-Aulu Marianna; Kaivo-oja Jari; Luukkanen Jyrki (Kaunas University of Technology, 2022)
European research and innovation policy highlights the importance of transnational scientific collaboration, International collaborations in science concentrates and magnifies resources for conducting research and foster innovation. Often, individual institutions, or even individual European countries, cannot provide the right capabilities by themselves. Joint facilities and Research Infrastructures (RIs) are therefore of high importance, and through Horizon 2020 and Horizon Europe nearly €5 bn EU funding is set aside for these institutions. Considering the large-scale funding and the perceived importance of RIs, a better understanding of their roles, functions, and usefulness is highly relevant to of European integration studies. While ‘Research Infrastructures’ has become a fixed terminology of EU-policy, conceptually defining RIs remain a matter of academic debate. We contribute to the “what is an RI?”-discussion by synthesizing existing literature and presenting novel empirical data from the energy domain mapping of the Horizon 2020-project Research Infrastructures in the International Landscape (RISCAPE). We provide insights into the process of mapping an hitherto largely unknown landscape of global Energy RIs. These insights touch upon both definitional issues relevant to the RI-field and methodological concerns for future landscape analyses. Finally, the article suggests that when it comes to energy research, RI-terminology might be misplaced as a catchall modern synonym for “gold standard world-class science”.